Merdeka Belajar Kampus Mengajar (MBKM) curriculum evaluation - Referen Piliano; Rosa Choerunnisa; Muhammad Sultan Alvaro; Shalita Aura Pranadinata; Angga Hadiapurwa; Ridha Pratama Rusli (Curricula: Journal of Curriculum Development, 2023)
Curriculum evaluation is an essential aspect in assessing the application of the curriculum in learning, with the development of the MBKM curriculum making learning changes in every tertiary institution. So, it is necessary to have a study related to evaluating the MBKM curriculum. The purpose of this research is to be able to examine the impacts and problems found in the MBKM curriculum. The approach used is qualitative with library study data collection. This study's results show that a positive and good response is received in evaluating the MBKM curriculum. MBKM is considered to be able to develop students' abilities. One of the developing abilities is the self-quality possessed by students. Even so, there are still some things that need to be improved. So far, the problem is that evaluations are mainly carried out summatively. For this reason, it is hoped that there will be improvements related to the MBKM curriculum and assessments using both summative and formative methods because they complement each other.